Pembelajaran Berdiferensiasi Terhadap Peningkatan Hasil Belajar Peserta Didik Gangguan Pemusatan Perhatian dan Hiperaktivitas (GPPH) - Yuda Ardi Saputra; Ayu Rizki Susilowati (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
Students with Attention Deficit and Hyperactivity Disorders (GPPH) find it difficult to learn conventionally because students tend to be hyperactive and have difficulty concentrating on the learning process. This affects the learning outcomes of students, especially in regular schools that organize inclusive education programs. This research is a Classroom Action Research (CAR) which aims to improve the learning outcomes of GPPH students through differentiation learning in class V. This research uses a qualitative research method through the distribution of instruments to research subjects of GPPH students in class V of Srirahayu Public Elementary School in the 2021 academic year/ 2022. The results showed that there was an increase in the mastery of GPPH students' learning outcomes from pre-cycle, implementation of cycle I, and cycle II. The results of the analysis of student learning outcomes in the pre-cycle revealed that there were no GPPH students who achieved mastery in Civics, Indonesian Language, Mathematics, Science, Social Sciences and SBdP subjects. In cycle I there was an increase in mastery of learning outcomes by 100% of GPPH students in Civics subjects, and 50% of GPPH students in Indonesian, Social Studies and SBdP subjects. In cycle II there was an increase in learning completeness of GPPH students up to 100% in all subjects. This shows that differentiated learning can improve the learning outcomes of GPPH students.